A Philosophy of Israel Education A Relational Approach - Chazan, Barry (Springer International Publishing : Imprint: Palgrave Macmillan, 2016)
This book develops a new philosophy of Israel education. "Person-centered" Israel education is concerned with developing in individual learners the ability to understand and make rational, emotional, and ethical decisions about Israel, and about the challenges Israel regularly faces, whether they be existential, spiritual, democratic, humanitarian, national, etc. Chazan begins by laying out the terms of the conversation then examines the six-pronged theory of "person-centered" Israel education to outline the aims, content, pedagogy, and educators needed to implement this program. Finally, the author meditates on what a transformation from ethnic to ethical education might look like in this context and others. Barry Chazan is Professor of Education and Founding Director of the Master of Arts in Jewish Professional Studies Program at the Spertus Institute of Jewish Learning and Leadership. He is Emeritus Professor at the Hebrew University of Jerusalem, Israel.